The Effect of Green Marketing Implementation, Stakeholder Collaboration, and Technological Innovation on the Marketing Effectiveness of Waste-Based Energy with Customer Satisfaction as an Intervening Variable - Agung Sutomo; Hamdan Hamdan (Harmony Management: International Journal of Management Science and Business, 2026)
The transition toward sustainable energy systems requires the transformation of renewable energy marketing strategies, particularly for waste-based energy. This study aims to analyze the effects of green marketing, stakeholder collaboration, and technological innovation on the marketing effectiveness of waste-based energy, with customer satisfaction as an intervening variable. A quantitative approach with a survey design was used. Data were collected from 300 respondents, comprising consumers and stakeholders at PT PLN (Persero) ’s waste-based energy processing units. Structural Equation Modeling (SEM) was used to analyze the data. The results indicate that green marketing, stakeholder collaboration, and technological innovation significantly influence customer satisfaction and the effectiveness of marketing. Furthermore, customer satisfaction significantly mediates the relationship between independent variables and marketing effectiveness. These findings emphasize the importance of integrating sustainable marketing strategies, multi-stakeholder synergy, and innovative technologies to enhance the competitiveness of waste-based energy products in the market. This study contributes to the theoretical development of renewable energy marketing models and provides practical implications for policymaking and green energy marketing strategies in Indonesia.